Directional Landscapes: Using Parametric Loudspeakers for Sound Reproduction in Art (2017)
As new technologies appear, the expressive palette of creators broadens. Parametric loudspeakers are one of such new technologies that makes it possible to direct sound as though it were a light beam. Since their debut in the market, they have thus far received little attention from part of the artistic world. Some peculiarities concerning the sound reproduction might explain why musicians in particular are hesitating to use an otherwise highly attractive acoustic innovation. Due to such peculiarities, a proper use of parametric loudspeakers in art must start with investigating a whole array of different topics (i.e. non-linear acoustics and ultrasonic transducers) in order to understand how this technology works and utilize it at its best. The result of our project is ultimately a sound installation that makes use of directional sound to ruminate on issues concerning sound perception and the responsible use of our sound environment. © 2016 Informa UK Limited, trading as Taylor & Francis Group.